2017
DOI: 10.1007/s10900-016-0304-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Metabolic Syndrome and Its Individual Components Among Midwestern University Students

Abstract: Michigan has the 17th highest adult obesity rate in the United States. Among college-aged adults between 18 and 25 years old, the rate of obesity was 11.6%. Obesity is a key precedent for the development of metabolic syndrome. Accordingly, the purpose of this study was to examine the prevalence of metabolic syndrome and its individual components among a sample of students at Central Michigan University. A cross-sectional survey was conducted among 462 students, aged 18-25 years, in Spring 2015 and Fall/Spring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 58 publications
1
16
1
Order By: Relevance
“…31 Moreover, the frequency of AO in this study was less than the frequencies observed in medical students from Ecuador (43.2%) 33 and in young health professionals (74.6% younger than 40 years) in Brazil (55.4%). 30 However, the frequency of low HDL-C in our study was higher than that observed in university students from the United States (12.6%) 43 and in young Brazilian health professionals (23.8%) 30 ; and it was lower than the frequency reported in Ecuadorian medical students (31.8%) 33 and in medical students from Mexico (59.1%). 31 The higher prevalence of AO may be attributable to the fact that Latin American populations are more susceptible to abdominal fat accumulation and to the development of insulin resistance and fatty liver than non-Hispanic white populations.…”
contrasting
confidence: 91%
See 1 more Smart Citation
“…31 Moreover, the frequency of AO in this study was less than the frequencies observed in medical students from Ecuador (43.2%) 33 and in young health professionals (74.6% younger than 40 years) in Brazil (55.4%). 30 However, the frequency of low HDL-C in our study was higher than that observed in university students from the United States (12.6%) 43 and in young Brazilian health professionals (23.8%) 30 ; and it was lower than the frequency reported in Ecuadorian medical students (31.8%) 33 and in medical students from Mexico (59.1%). 31 The higher prevalence of AO may be attributable to the fact that Latin American populations are more susceptible to abdominal fat accumulation and to the development of insulin resistance and fatty liver than non-Hispanic white populations.…”
contrasting
confidence: 91%
“…41,42 These two components were also the most frequently reported MS components in other studies on general populations in Latin American countries such as Mexico, 16,19 Venezuela, 17 Argentina, Chile, and Uruguay, 15 in addition to university students in the United States, 43 medical students in Ecuador 33 and Mexico, 31 and health professionals in Brazil 30 and Mexico. [26][27][28] However, the frequency of AO observed in this study is higher than that reported in university students in the United States (22%) 43 and in medical students from Mexico (17.8%). 31 Moreover, the frequency of AO in this study was less than the frequencies observed in medical students from Ecuador (43.2%) 33 and in young health professionals (74.6% younger than 40 years) in Brazil (55.4%).…”
mentioning
confidence: 84%
“…Generally, metabolic syndrome is closely related with smoking, drinking alcohol, obesity, body mass index (BMI), gender, age, stress, exercise, hypertension, chronic disease, family history, and concerns on health (Fan et al, 2019;Jamee et al, 2019;Li et al, 2016;Mercado et al, 2015;Pérez et al, 2019;Yahia et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…MS prevalence is estimated to increase with age; the prevalence is 20–25% in adults and 0.6–13% in college students in the USA [7,8,9]. Findings from the Young Adult Health Risk Screening Initiative study, conducted on 2722 college students aged 18–24 years, showed that 3% and 10% of female and male participants, respectively, had MS, and 54% and 77% of female and male participants, respectively, had at least one risk factor for MS [7].…”
Section: Introductionmentioning
confidence: 99%